Heart and soul [compact disc, unabridged] - Binchy, Maeve, 1940-2012 (Books on Tape, 2009)
Dr. Clara Casey was certain the senior cardiologist position was hers. Instead, she is offered the thankless job of establishing a rehab heart clinic that's woefully under-funded. She reluctantly accepts the job, but promises to leave after one year. Clara quickly assembles a diverse and capable staff, all of whom pitch in to help heal the lives of their demanding and sometimes difficult patients. Before long, they have established the clinic as an integral part of the community. After the year is up, Clara struggles with the decision to leave, knowing that her time there has changed her life forever.